Manajemen Prasarana Pembelajaran: Pengalaman Di Miracle Language Center, Narathiwat, Thailand Dan Indonesia - Firanita Putri; Tawfiq Sarehmansor; Dakir; Muzakki (Gudang Jurnal Multidisiplin Ilmu, 2024)
School infrastructure management is a utilization process whose target is educational equipment, such as school equipment, library equipment, teaching media, and other equipment. Management of school equipment is realized as a process consisting of certain systematic steps. Miracle Language Center is a garden house that was founded on February 2 2020 by a foundation body, namely the Diamond Family. The Miracle Language Center in Mueang, Narathiwat, Southern Thailand is home schooling. The facilities and infrastructure at the Miracle Language Center include a prayer room, library, men's dormitory, women's dormitory and toilets. This study uses a qualitative method. The qualitative method aims to describe data analysis in a narrative manner that emphasizes analysis or descriptiveness. Data collection was carried out using three data collection techniques, namely observation, interviews and documentation. Management of facilities and infrastructure is very important because by managing the facilities and infrastructure of educational institutions, their use will be maintained and clear. Here the researcher will describe the management of facilities and infrastructure at the Miracle Language Center, Narathiwat, Thailand. Starting from planning to eliminating existing educational facilities and infrastructure at the foundation